Boosting Oxygen Reduction Performance of Manganese Oxide in Alkaline Media by Three-Dimensional Highly Ordered Conductive Porous Framework - Xiao, Xiaofen; Fang, Zhengsong; Yu, Dingshan (Frontiers in Materials, 2019)
MnO2 has been widely used as alternative candidates for oxygen reduction reaction owing to their abundance, low cost and environmental compatibility. However, bulk MnO2 as electrocatalysts are always suffering from serious active sites accumulation and poor conductivity, which lead to low utilization of catalysts and sluggish reaction kinetics. In view of this, we fabricate a 3D highly ordered porous MnO2@Ni-pc nanocomposite and significantly enhance ORR performance of MnO2 with high onset potential of 1.04 V and half-wave potential of 0.89 V as well as a large limiting current density of 4.07 mA cm-2, being even comparable to the commercial Pt/C. This nano-engineering technique is supposed to suitable for various catalysts that can be attached on the 3D highly ordered porous framework, which provides new opportunities in designing electrode structures for boosting the performance of bulk materials.